The Fun of Being Coordinator, Looking Ahead, Meet ACE Authors - James P. Chapman (Journal of Applied Communications, 1978)
Commentary from the AAACE Headquarters Coordinator in the last issue to be published by the Ohio State AAACE Headquarters crew; and additional editorial back matter for this issue.